EVALUASI DAMPAK PROGRAM PENANGGULANGAN KEMISKINAN BERSASARAN DI PROPINSI D.I. JOGJAKARTA - Awan Santosa; Dadit G. Hidayat; Puthut Indroyono (Journal of Indonesian Economy and Business (JIEB), 2003)
This research tries out the ESCAP’s manual on Impact Evaluation for PovertyAlleviation Program in the province of Yogyakarta Special Region. There are several indicators of program evaluation in this method, i.e.: income indicator, poverty reduction, efficiency in program delivery, financial viability, and other aspects. The program clasified into two categories, Self Employment Program (SEP’s) and Public Work Program (PWP’s). SEP carried out by giving revolving block grant to the poor and PWP is carried out by developing physical building as public utilities. The research produces quantitative estimate of program success/failure, which can be useful to evaluate or to improve the implementation of poverty alleviation programs in the future.Keywords: targeted Poverty Alleviation Program, self employment program, public work program, income generating, poverty reduction, efficiency in programdelivery, financial viability.